Query expansion using lexical-semantic relations - Lee, Yuet Meng. (2010)
This study tries to find the types of lexical-semantic relations that are effective for query expansion. Fox (1980) had done similar work in this field and concluded that all types of relations are useful except antonyms. This paper attempts to replicate Fox's (1980) work and extend it by studying the effectiveness of individual types of relations. Using only 1 query from the TREC test collection and text paragraphs from the 1994 Financial Times database, relations between word pairs are studied using Fox's (1980) list of 73 classes of lexical-semantic relations. Experiments to extend the query with relevant relations are conducted to find the effective relations for query expansion.